1, 2-Dimyristoyl-sn-glycero-3-phosphocholine (DMPC) increases Carmofur stability and in vitro antiproliferative effect. (2015) - Domracheva, Ilona; Muhamadejev, Ruslan; Petrova, Marina; Liepinsh, Edvards; Gulbe, Anita; Shestakova, Irina; Duburs, Gunars; Arsenyan, Pavel
Graphical abstract: Highlights: DMPC addition stabilizes Carmofur at neutral pH. We report considerable increase of Carmofur cytotoxicity. It opens a way for the drug delivery of Carmofur in neutral and basic media. Abstract: Addition of DMPC considerably inhibits the degradation of Carmofur in neutral phosphate buffer solutions and this drug becomes less influenced by pH. Carmofur stabilization at neutral pH caused by DMPC addition for in vitro studies was characterized and monitored by 1 H NMR. Antiproliferative activity studies on various tumor cell lines showed considerable increase of Carmofur ability to prevent tumor cell growth, when it is added as a mixture with DMPC. This technique opens a way for Carmofur drug delivery in neutral and basic media.